2013
DOI: 10.1161/atvbaha.113.301362
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Von Willebrand Factor Promotes Blood–Brain Barrier Flexibility and Provides Protection From Hypoxia and Seizures in Mice

Abstract: Objective Aberrant blood-brain barrier (BBB) permeability is a hallmark pathology of many central nervous system diseases. von Willebrand factor (VWF) is stored in endothelial Weibel-Palade bodies from where it is released upon activation into plasma and basement membrane. VWF’s role in endothelial homeostasis is unclear. The goal of this study was to assess the role of VWF in disease models associated with increased BBB permeability. Approach and Results We did not find any differences in BBB permeability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 67 publications
(76 reference statements)
4
62
0
1
Order By: Relevance
“…38 In this study, we found that P berghei infection was associated with a significant increase in BBB permeability in both WT and VWF 2/2 mice. Interestingly, however, the degree of ECM-associated enhanced BBB permeability was significantly attenuated in the VWF 2/2 mice compared with WT controls.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…38 In this study, we found that P berghei infection was associated with a significant increase in BBB permeability in both WT and VWF 2/2 mice. Interestingly, however, the degree of ECM-associated enhanced BBB permeability was significantly attenuated in the VWF 2/2 mice compared with WT controls.…”
mentioning
confidence: 50%
“…54 In addition, endothelial VWF has recently been shown to play an important role in modulating permeability of the BBB under different pathological conditions. 38,39 Although the underlying biological mechanisms remain poorly understood, enhanced permeability of the BBB has also been implicated in the pathogenesis of CM. [55][56][57][58] We therefore investigated BBB permeability in VWF 2/2 mice compared with WT mice following infection with P berghei.…”
Section: Ecm-induced Bbb Permeability Is Attenuated In Vwf-deficient mentioning
confidence: 99%
See 1 more Smart Citation
“…In hCMEC/D3 cell layers, we analysed the expression of von Willebrand factor (vWF), a protein that is involved in regulation of coagulation and moreover is a central regulator of permeability and flexibility of the endothelial cell layer within the BBB. 18 In addition, we examined the expression of VE-cadherin and b-catenin, proteins required for the maintenance of endothelial barrier integrity and CNS homeostasis, 19 as well as the tight junction protein ZO-1. We observed no alterations in the protein expression of these proteins during adaption and subsequent culture of CMEC in CTM/ECM medium compared with ECM medium (Figure 4(b)).…”
Section: Detection Of Typical Cortical and Endothelial Cell Marker Prmentioning
confidence: 99%
“…HCMEC/D3 cell layers expressed central marker proteins known to regulate BBB integrity and flexibility in vivo, such as vWF, VE-cadherin, ZO-1, and b-catenin. [4][5][6]9,10,18,19 Furthermore, this model is able to reflect critical aspects of neuroinflammation, as depicted by its ability to specifically reproduce a cytokineinduced disruption of the endothelial barrier associated with subsequent alterations in neural cell morphology, increased neural cell death, and diminished expression of neural differentiation marker proteins. Our results are in agreement with the findings from studies in mice that analysed the development of the neocortex under inflammatory conditions.…”
Section: -10mentioning
confidence: 99%